Tumorigenic fragments of APC cause dominant defects in directional cell migration in multiple model systems - Scott A. Nelson; Zhouyu Li; Ian P. Newton; David Fraser; Rachel E. Milne; David M. A. Martin; David Schiffmann; Xuesong Yang; Dirk Dormann; Cornelis J. Weijer; Paul L. Appleton; Inke S. Näthke (The Company of Biologists, 2012)
SUMMARY Nonsense mutations that result in the expression of truncated, N-terminal, fragments of the adenomatous polyposis coli (APC) tumour suppressor protein are found in most sporadic and some hereditary colorectal cancers. These mutations can cause tumorigenesis by eliminating β-catenin-binding sites from APC, which leads to upregulation of β-catenin and thereby results in the induction of oncogenes such as MYC. Here we show that, in three distinct experimental model systems, expression of an N-terminal fragment of APC (N-APC) results in loss of directionality, but not speed, of cell motility independently of changes in β-catenin regulation. We developed a system to culture and fluorescently label live pieces of gut tissue to record high-resolution three-dimensional time-lapse movies of cells in situ. This revealed an unexpected complexity of normal gut cell migration, a key process in gut epithelial maintenance, with cells moving with spatial and temporal discontinuity. Quantitative comparison of gut tissue from wild-type mice and APC heterozygotes (APCMin/+; multiple intestinal neoplasia model) demonstrated that cells in precancerous epithelia lack directional preference when moving along the crypt-villus axis. This effect was reproduced in diverse experimental systems: in developing chicken embryos, mesoderm cells expressing N-APC failed to migrate normally; in amoeboid Dictyostelium, which lack endogenous APC, expressing an N-APC fragment maintained cell motility, but the cells failed to perform directional chemotaxis; and multicellular Dictyostelium slug aggregates similarly failed to perform phototaxis. We propose that N-terminal fragments of APC represent a gain-of-function mutation that causes cells within tissue to fail to migrate directionally in response to relevant guidance cues. Consistent with this idea, crypts in histologically normal tissues of APCMin/+ intestines are overpopulated with cells, suggesting that a lack of migration might cause cell accumulation in a precancerous state.